Assessment Of Phenotypic Diversity And Farmers‟ Knowledge Of Cultivation And Utilization Of Pigeon Pea [Cajanus Cajan (L.) Millspaugh] In Benin - Ayenan, M.A.T (University of Ghana, 2016)
Pigeon pea plays a significant role in smallholder farmers‟ subsistence. In Benin, there is a dearth of information on the genetic diversity present in the crop. Indigenous knowledge used in folk medicines, taxonomy, crop management and seed system have not been assembled and documented. This study aimed at assessing farmers‟ knowledge related to pigeon pea cultivation and uses and genetic diversity of pigeon pea germplasm in Benin. Participatory Rural Appraisal including individual interview (n=302) and focus group was conducted. A triple lattice square design was used for agro-morphological characterization of 49 accessions. Results revealed that 98% of the pigeon pea growers practiced intercropping. Difficulty to harvest pulses, low productivity and lack of quality seed were the main factors constraining pigeon pea production. High yielding, early maturing and pod resistance to borers were the main farmers‟ preferred traits. Varietal naming of pigeon pea varieties was based on morphological traits, the origin of the variety and the perception of farmers on the variety. Based on the Shannon-Weaver Diversity Index (H‟), the less and the most polymorphic qualitative traits in the germplasm were pod hairiness (H‟=0) and flower streak colour (H‟=1.88), respectively. Pod yield (CV=31.4%), seed yield (CV=35.1%), number of pod per plant (CV=31%) were the most variable quantitative traits in the pigeon pea collection. The PCA revealed that the first four principal components accounted for 78.96% of the total variation. The traits which contributed more to the variation in the germplasm were plant height, number of raceme per plant, pod bearing length, days to 50% flowering, days to 75% maturity, pod yield, seed yield, number of seeds per pod, number of pod per plant and 100 seeds weight. The clustering analysis using Tocher’s method based on the Euclidean distance separated the accessions into 10 clusters with a clear cut between breeding materials obtained from IITA Ibadan and traditional cultivars collected in Benin. Significant association with biological interest (r>0.71, P<0.05) was found between number of raceme and days to 50% flowering, days to 75% maturity and days to 50% flowering, pod bearing length and days to 50% flowering. Besides shelling percentage, all the traits showed medium or high heritability. The highest responses to selection were recorded for seed yield (GA%=48.83%), pod yield (GA% = 47.17%) and number of pod per plant (GA%=44.61%). This study provided a sound basis for designing appropriate strategies for sustainable production of pigeon pea in Benin and for successful variety development and introduction. In addition, Benin pigeon pea germplasm could potentially be exploited for yield improvement in international pigeon pea breeding programmes.
Thesis (MPhil)
Keywords: Phenotypic Diversity; Farmers; Knowledge Of Cultivation; Utilization Of Pigeon Pea; Cajanus Cajan (L.) Millspaugh